2019
DOI: 10.1096/fj.201900398rr
|View full text |Cite
|
Sign up to set email alerts
|

Enteric dysbiosis is associated with sepsis in patients

Abstract: Sepsis is defined as a life‐threatening organ dysfunction caused by a dysregulated host response to microbial infection. For decades, the potential role of gut microbiota in sepsis pathogenesis has been revealed. However, the systemic and functional link between gut microbiota and sepsis has remained unexplored. To address this gap in knowledge, we carried out systematic analyses on clinical stool samples from patients with sepsis, including 16S rDNA sequencing, metabolomics, and metaproteomics analyses. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 50 publications
3
50
1
Order By: Relevance
“…Animal studies have demonstrated conflicting results regarding specific inflammatory pathways, reflecting the complexity of the relationship between the gut microbiome and the immune system. For example, in a mouse model of Streptococcus pneumoniae sepsis, pre-treatment with oral antibiotics prior to sepsis onset was associated with lower levels of lung TNF-α, a pro-inflammatory cytokine [25], whereas others have shown the opposite effect of gut microbiome depletion on TNF-α [21,22,[37][38][39]. Despite differences in specific cytokine expression between studies, the overall effect of alteration of normal gut microbiome structure prior to sepsis onset appears to be a more robust inflammatory response to sepsis [21,22,25,[37][38][39][40][41].…”
Section: Altered Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have demonstrated conflicting results regarding specific inflammatory pathways, reflecting the complexity of the relationship between the gut microbiome and the immune system. For example, in a mouse model of Streptococcus pneumoniae sepsis, pre-treatment with oral antibiotics prior to sepsis onset was associated with lower levels of lung TNF-α, a pro-inflammatory cytokine [25], whereas others have shown the opposite effect of gut microbiome depletion on TNF-α [21,22,[37][38][39]. Despite differences in specific cytokine expression between studies, the overall effect of alteration of normal gut microbiome structure prior to sepsis onset appears to be a more robust inflammatory response to sepsis [21,22,25,[37][38][39][40][41].…”
Section: Altered Immune Responsementioning
confidence: 99%
“…Several prospective cohort studies have identified an association between decreased gut microbiome diversity in sepsis and higher relative abundance of potentially pathogenic bacteria including aerobic gram negatives [39,46,56,[59][60][61]. The earliest study to examine microbiome changes in critically ill patients showed that patients with systemic inflammatory response syndrome (SIRS) had lower abundance of obligate anaerobes, and their gut microbiomes were enriched with potential pathogens such as Staphylococcus and Pseudomonas [46].…”
Section: Sepsis Worsens Gut Microbiome Disruptionmentioning
confidence: 99%
“…Schnabl has shown that gut dysbiosis seems to participate in the disruption of intestinal epithelial tight junctions and imbalance in the proliferation and apoptosis of IECs [13]. Recent research has found that gut microbial dysbiosis leads to serious liver injury in mice after cecal ligation and puncture [47]. Several mechanisms may answer this phenotype.…”
Section: The Role Of Bacterial Clearance and Gut Dysbiosis In The Gutmentioning
confidence: 99%
“…The syndrome can be induced by a wide variety of microbes and, by de nition, involves a maladaptive response to a pathogen [5]. The gastrointestinal (GI) tract has long been hypothesized to play an integral role in the pathophysiology of sepsis, by both driving and perpetuating multiple organ dysfunction [8,9].…”
Section: Introductionmentioning
confidence: 99%